Utilizing ICT to Promote Motivation towards Language Learning among Engineering Students - Haslinda, Hashim; Hafizoah, Kassim; Noor Raha, Mohd Radzuan (2006)
Rapid advancement of technology and the impact of globalization have breathed new changes into our lives. These changes bring new challenges to every aspect of life in the digital world we live in today. Being part and parcel of the digital package, Information and Communication Technology (ICT) plays a vital role to ensure that the needs for these new tides are met, particularly within the area of language education. Consequently, many language educators are urged to integrate ICT into their language classes, above all, as a means for student motivation. On this basis, this paper attempts to unearth the potentials of language learning enhancement through the utilization of ICT as motivational tool. Thus, this move will look beyond the conventional 'board and chalk' approach at language teaching and learning. Hence, it is essential that we identify the ICT tools that can motivate learners and their significant effects on student motivation in language learning. This study is conducted in KUKTEM, Pahang, Malaysia.